1983
DOI: 10.1128/jb.154.3.1263-1268.1983
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-controlled resistance to copper in Escherichia coli

Abstract: The copper resistance of a strain of Escherichia coli isolated from the effluent of a piggery where pigs were fed a diet supplemented with copper sulfate was controlled by a conjugative 78-megadalton plasmid designated pRJ1004. Plasmid pRJ1004 exhibited surface exclusion and incompatibility with standard plasmids belonging to incompatibility groups I1 and K. Sensitive strains of E. coli K-12 were unable to form colonies on nutrient agar containing more than 4 mM copper, whereas transconjugants which harbored p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(72 citation statements)
references
References 20 publications
1
70
1
Order By: Relevance
“…But in respect of Cu, the level of resistance was almost the same at the range of 20 mmol 1-' both for Acidiphilium strains and an Escherichia coli isolate (Tetaz and Luke 1983). It may therefore be suggested that Acidzphillum strains, in general, probably represent the highest metal-tolerant bacteria among the heterotrophs although their growth was inhibited at a very low concentration of Hg and Ag (Bhattacharyya et al 1991).…”
Section: Resultsmentioning
confidence: 95%
“…But in respect of Cu, the level of resistance was almost the same at the range of 20 mmol 1-' both for Acidiphilium strains and an Escherichia coli isolate (Tetaz and Luke 1983). It may therefore be suggested that Acidzphillum strains, in general, probably represent the highest metal-tolerant bacteria among the heterotrophs although their growth was inhibited at a very low concentration of Hg and Ag (Bhattacharyya et al 1991).…”
Section: Resultsmentioning
confidence: 95%
“…An E. coli copper resistance plasmid, pRJ 1004, was found in a strain isolated from the effluent of a piggery [77] where copper sulfate, used as a food supplement, possibly acted as a selective agent. Inducible resistance to copper conferred by pRJl004 was found to be due to decreased metal uptake [78].…”
Section: "Fhe E Coli Systemmentioning
confidence: 99%
“…1989;Brown ef a/., 1994). The genetic approach involved characterization of a plasmid system that confers resistance to high copper levels (Tetaz and Luke. 1983;Reuch, 1986;Brown etai, 1994) and, inaddition, isolation of chromosomal mutations that result in 'hypersensitivity' of the Esdieridiia co//ceil to copper salts (Rouch, 1986;Rogers eta!..…”
Section: Introductionmentioning
confidence: 99%